2021
DOI: 10.3390/pr9091633
|View full text |Cite
|
Sign up to set email alerts
|

Data Driven Detection of Different Dissolved Oxygen Sensor Faults for Improving Operation of the WWTP Control System

Abstract: Sensor faults frequently occur in wastewater treatment plant (WWTP) operation, leading to incomplete monitoring or poor control of the plant. Reliable operation of the WWTP considerably depends on the aeration control system, which is essentially assisted by the dissolved oxygen (DO) sensor. Results on the detection of different DO sensor faults, such as bias, drift, wrong gain, loss of accuracy, fixed value, or complete failure, were investigated based on Principal Components Analysis (PCA). The PCA was consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In ref. 21, a data-driven approach based on PCA is employed to detect various dissolved oxygen (DO) sensor faults in WWTPs. The study focuses on biases, drifts, gains, accuracy losses, fixed values, and complete failures of DO sensors.…”
Section: Introductionmentioning
confidence: 99%
“…In ref. 21, a data-driven approach based on PCA is employed to detect various dissolved oxygen (DO) sensor faults in WWTPs. The study focuses on biases, drifts, gains, accuracy losses, fixed values, and complete failures of DO sensors.…”
Section: Introductionmentioning
confidence: 99%
“…It can be used in many different fields where detecting abnormalities or outliers is essential for maintaining the system's health, sustaining security, or optimizing processes. There are various examples of problems involving fault detection, such as frauds [1], network intrusions [2], manufacturing defects [3], anomaly detection in time series data [4], cybersecurity [5,6], microfluidics [7][8][9][10], and most importantly, anomaly detection in wastewater treatment plants [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Kazemi et al [16] showed that incremental PCA was able to distinguish between time varying events and faults in simulated data, while Kazemi et al [17] investigated a number of technics including Support Vector Machine, Ensemble Neural Network and Extreme Learning and found that they performed better than a PCA based method after testing on simulated data. Luca et al [18] applied PCA and statistic for fault detection in DO sensors in simulated data and stated that the method was successful in detecting the faults. Mali and Laskar [19] proposed an optimized Monte Carlo deep neural network and were able to detect faults of low magnitude in simulated data.…”
Section: Introductionmentioning
confidence: 99%